Excessive Release of Inorganic Polyphosphate by Als/Ftd Astrocytes Causes Non-Cell-Autonomous Toxicity to Motoneurons - Madrid-Montecinos, R; Pertusa-Pastor, M (Cell Press, 2022)
Non-cell-autonomous mechanisms contribute to neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), in which astrocytes release unidentified factors that are toxic to motoneurons (MNs). We report here that mouse and patient iPSC-derived astrocytes with diverse ALS/FTD-linked mutations (SOD1, TARDBP, and C9ORF72) display elevated levels of intracellular inorganic polyphosphate (polyP), a ubiquitous, negatively charged biopolymer. PolyP levels are also increased in astrocyte-conditioned media (ACM) from ALS/FTD astrocytes. ACM-mediated MN death is prevented by degrading or neutralizing polyP in ALS/FTD astrocytes or ACM. Studies further reveal that postmortem familial and sporadic ALS spinal cord sections display enriched polyP staining signals and that ALS cerebrospinal fluid (CSF) exhibits increased polyP concentrations. Our in vitro results establish excessive astrocyte-derived polyP as a critical factor in non-cell-autonomous MN degeneration and a potential therapeutic target for ALS/FTD. The CSF data indicate that polyP might serve as a new biomarker for ALS/FTD. © 2022 Elsevier Inc.